ALF 1990-1995 - Örebro county - Swedish Working Life Fund (Swedish Working Life Fund, 1996)
During the period 1990-1995 approximately 25 000 workplace programmes were carried out with financial contribution from the Swedish Working Life Fund (ALF). The aim of the programmes was to develop labour organisations, to increase competence, to improve work environment, and to make rehabilitation attempts within working life. System ALF includes information on name and address of the establishment, contact person, organisation number, branch, SNI-code, number of men and women employed, number of men and women affected by the project, calculated total cost for the project divided on grants from the fund, contribution from the establishment and other financing, start and calculated conclusion of the project, savings for the establishment and for national insurance, final application and granted funds, and type of measures taken. This is a copy of the original database used at the Swedish Working Life Fund. The system can only be distributed complete and requires 190 Mb of hard disk space. Data is also available in a format adapted for statistical analysis.

En sammanställning av de omkring 25 000 arbetsplatsprogram som utfördes av Arbetslivsfonden mellan 1990 och 1995, uppdelad i ett dataset för varje län. Det sista datasetet, 026, är en kopia av Arbetslivsfondens ursprungliga databas.

This dataset includes all projects applying for grants where the place of work is localized within Örebro county and contains all information available in the administrative system of the Swedish Working Life Fund, System ALF.
ALF 1990-1995 - Örebro län
Keywords: LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; LABOUR MARKET; ARBETSMARKNAD; EMPLOYMENT POLICY; SYSSELSÄTTNINGSPOLITIK; Health care services and policies; Hälso- och sjukvårdstjänster och -politik; Employment; Sysselsättning; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap